1995
DOI: 10.2214/ajr.165.6.7484585
|View full text |Cite
|
Sign up to set email alerts
|

An imaging algorithm for the differential diagnosis of adrenal adenomas and metastases.

Abstract: OBJECTIVE.The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0
9

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(65 citation statements)
references
References 21 publications
0
56
0
9
Order By: Relevance
“…The advantages of MRI over CT are its lack of radiation exposure, lack of iodine-based contrast media and its superior tissue contrast resolution. For the differentiation of benign and malignant adrenal masses, the MRI technique of chemical shift imaging is most commonly used (60,61,62,63,64,65). Chemical shift imaging relies on the fact that, within magnetic fields, protons in water vibrate at a slightly different frequency than protons in lipid.…”
Section: Short Overview On Adrenal Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…The advantages of MRI over CT are its lack of radiation exposure, lack of iodine-based contrast media and its superior tissue contrast resolution. For the differentiation of benign and malignant adrenal masses, the MRI technique of chemical shift imaging is most commonly used (60,61,62,63,64,65). Chemical shift imaging relies on the fact that, within magnetic fields, protons in water vibrate at a slightly different frequency than protons in lipid.…”
Section: Short Overview On Adrenal Imagingmentioning
confidence: 99%
“…• Included: We identified 37 studies for inclusion in the systematic review (49,52,61,79,80,81,82,83,84,85,86,87,88,89,90,91,92,93,94,95,96,97,98,99,100,101,102,103,104,105,106,107,108,109,110,111,112), with only 18 of them fulfilling the criteria for inclusion in the actual meta-analysis (61,79,80,81,82,83,84,85,86,87,88,89,90,91...…”
Section: Assessment Of the Risk Of Malignancy By Imaging (Question 1a)mentioning
confidence: 99%
“…78,79,84 Attenuation values seem to have better performance than size in diagnosing adrenal malignancy. 81,85 A threshold of 10 HU is the most widely advocated, 1-3,21,81,83,84,86-88 displaying a sensitivity-to-specificity ratio of 79%:96%, whereas a threshold of 0 HU changes this ratio to 47%:100%. 81 This is in accordance with a meta-analysis of ten studies designed to determine an optimal threshold for differentiating benign from malignant lesions, which showed that a threshold of 10 HU had 71% sensitivity and 98% specificity for characterizion of adrenal masses.…”
Section: Non-functional Imaging Modalitiesmentioning
confidence: 99%
“…All CT scans were blinded and independently reviewed by two experienced radiologists using standardized criteria, commonly used for adrenal gland investigations (Lee et al, 1991;McNicholas et al, 1995;Korobkin et al, 1996;Szolar and Kammerhuber, 1997;Cirillo et al, 1998;Pena et al, 2000;Caoili et al, 2002;Kebapci et al, 2003). If discordant opinions were recorded, an additional evaluation was carried out by a third operator.…”
Section: Radiological Parameters With Benign/malignant Criteriamentioning
confidence: 99%